Public Policies toward Aboriginal Peoples: Attitudinal Obstacles and Uphill Battles. Issue 2 (16th December 2015) - White, Stephen; Atkinson, Michael M.; Berdahl, Loleen; McGrane, David
Abstract: This paper examines public attitudes towards aboriginal policy in Canada, focusing on evidence from two surveys conducted in Saskatchewan, a province with a large and growing Aboriginal population. We show that although non-Aboriginals are collectively divided on Aboriginal public policies, expressing considerable support for some, but strong reservations when it comes to others; the individual-level evidence indicates that there is a single Aboriginal policy agenda in the minds of non-Aboriginal Canadians. Support for, and opposition to, the privileging of Aboriginal claims is structured in part by prejudice toward outgroups but also by non-Aboriginal people's more general position on the role of government in society. Moreover, the impact of positions about the role of government in society on attitudes toward Aboriginal policies is moderated by people's level of political sophistication: the more educated and politically interested they are, the greater the impact of those ideological views. Résumé: Ce texte examine les attitudes publiques envers la politique autochtone au Canada, en se concentrant sur deux enquêtes menées en Saskatchewan, une province avec une grande population autochtone. Nous montrons que, bien que les non-Autochtones sont collectivement divisés sur les politiques publiques autochtones, exprimant un soutien considérable pour certains, mais ayant de fortes réserves pour d'autres, la preuve au niveau individuel indique qu'il y a un seul agenda politique autochtone dans l'esprit des Canadiens non-autochtones. Le soutien et l'opposition aux revendications autochtones est structuré en partie par les préjugés envers les groupes externes, mais aussi par la position des non-Autochtones plus générale sur le rôle du gouvernement dans la société. En outre, l'impact des positions sur le rôle du gouvernement dans la société sur les attitudes envers les politiques autochtones est animé par le niveau de sophistication politique des gens: plus ils sont instruits et politiquement intéressés, plus grand est l'impact de ces visions idéologiques.